PELAKSANAAN ASAS KONTRADIKTUR DELIMITASI DALAM PROSES PENDAFTARAN TANAH SISTEMATIS LENGKAP (Studi Kasus di Kantor Pertanahan Kabupaten Boyolali) - ANGGONO, SETYO (Dinamika Hukum, 2019)
The purpose of this study is to: 1) Review and analyze the application of the principle of kontradiktur delimitation in the implementation of a systematic registration of the Land Office in Boyolali Regency. 2) review and analyze the factors that hinder the application of the principle of kontradiktur delimitation in the implementation of a systematic registration of the Land Office in Boyolali Regency. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained the conclusion that the implementation of the principle of delimitation of kontradiktur especially in the land registration process systematically complete Land Office in Boyolali Regency has been running properly, because the application of the principle of delimitation of kontradiktur done at the moment before the clerk measure measurements, the borders must be present and show the boundaries of the land was at once put up signs on the boundary limits agreed upon. After that party that borders on signing the registration field, namely sheet sheet image measure as proof that the principle of delimitation of kontradiktur filled the time limit of the assignment and measurements. Fakor – factors that inhibit in the implementation of the principle of delimitation of kontradiktur on the determination of the boundaries of the land registration process in, among others, the existence of a dispute over land boundaries, land is not hooked up to the PIN, so that the boundaries of his land is not clear, it is difficult in measurement and mapping, the parties to both the applicant or the owner of the land that borders can not be present at the time of determination of the boundaries of land, it is hindered in the measurement so that slow down the completion of land registration. Fix IE dispute resolution limit conversationally, peg mounting mark land boundaries, delaying the setting of boundaries or by power of attorney. Keywords: Contradictoire Delimitatie, Complete Systematic Land Register.